Homeownership intention among young people in Selangor: the influence factors / Nurellya Ngadiman and Nur Fatihah Soleh Huddin - Ngadiman, Nurellya; Soleh Huddin, Nur Fatihah (2022)
This study was conducted among young people in Selangor to know the factors that influence homeownership intention. Housing is one of the necessities of life for us to shelter and protect ourselves. This study was also conducted for young people between 20 to 40 years old who live and work in Selangor. The researchers found a gap from the previous study followed by the dependent variables. To answer the research objective, the researchers conducted a quantitative method that influenced young people in Selangor by questionnaire in google form. Finding of this study shows that the most respondent was in the group of age 23 to 25 years old (49.5 percent) in this research. There is no significant difference between the determinant factors (housing attribute, housing cost, housing affordability and housing location and environment) of homeownership intention across their demographic profiles (age and monthly income), F(6,379)=1.263, p=0.274, p>0.05. The most determinant factors was found to be the housing location and environment where it has the strongest influence on the homeownership intention among the young people (β=0.317, p=0.000). Based on the discussion on the findings, this study proposed several recommendations such as stabilizing finance, reviewing housing affordability, promoting good housing development, and building more housing development at strategic location.